Psychological distress among adolescents of different ethnic groups in Malaysia - Janon, Nazariah Shar'ie (International Islamic University Malaysia, 2019)
Adolescence is a stage in human life where children seek autonomy and identity, are more prone to peer influence and deviant behaviour and frequently experience unstable emotional feelings. The changes experienced by adolescents and how they react to the changes highly depend on their culture, context and religious values. As a result, adolescents, regardless of their ethnic origin, are likely to experience psychological disturbance in the process of making adjustment. This study aims to investigate whether there is a difference in psychological distress experienced by adolescents of different ethnic groups. Five hundred and seventy-one adolescents (Malay, Chinese and Indian) were recruited from secondary schools in several states in Malaysia. A set of questionnaire that consists of demographic questions and statements from the General Health Questionnaire-12 (GHQ-12) that measure psychological distress was given to each participant. Based on the one-way analysis of variance, there is a significant different in the score of GHQ across ethnic groups. The mean score of Malay adolescents is significantly different from the mean score of Chinese adolescents. The mean score of Indian adolescents however, is not significantly different from the mean scores of the Malay and Chinese adolescents. These findings provide new knowledge for school counselling services regarding ethnic differences in psychological distress and inform the way forward for future research in the field of adolescent psychology.